Research on supply chain finance products at standard chartered bank = Nghiên cứu về sản phẩm tài trợ chuỗi cung ứng tại ngân hàng STANDARD CHARTERED - Nguyễn, Thu Minh (2020)
The first chapter explores current development of SCF. The importance of SCF is briefly presented in this chapter. The researcher also provides rationales of choosing the studied topic. Research objectives and research questions are proposed. This chapter highlights the scope of work and what the contribution of the thesis. The second chapter mentions the concept of supply chain and supply chain management before going further to the definitions of SCF. Then, framework of SCF is discussed along with its key components, including the actors, the levers, and the objects. The researcher provides the understandings about what the key successful factors of SCF in this chapter. The third chapter proposes research methodology to be used to fulfill research objectives and to answer research questions effectively. The data collection method and process are also proposed in this chapter. The method of data analysis and the sample size for data collection process are mentioned accordingly. The fourth chapter aims to extract the findings from the data collection. It covers the discussion of the case study of Standard Chartered Bank and how key successful factors to SCF programs to be maintained in the commercial bank. This chapter covers obstacles in the bank‟s managers regarding to the implementation and operation of SCF programs. The last chapter summarizes key findings from previous chapters. It is also designed to provide the recommendations to the banks‟ managers to manage their SCF process and to develop the SCF programs effectively by offering the most suitable products to bring benefits for their customers and to be able to position their reputation on the competitive financial market.